Indirect Treatment Comparison between Ribociclib Combined with Non-Steroidal Aromatase Inhibitors and Ovarian Function Suppression vsTamoxifen in Premenopausal Women with Early Breast Cancer Indirekter Behandlungsvergleich von Ribociclib kombiniert mit nichtsteroidalen Aromatasehemmern und ovarieller Funktionsunterdrückung mit Tamoxifen bei prämenopausalen Frauen mit Brustkrebs im Frühstadium - Lüftner, Diana; Banys-Paluchowski, Maggie; Hartkopf, Andreas D.; Hörner, Manuel; Janni, Wolfgang; Langanke, Dagmar; Müller, Volkmar; Schneeweiss, Andreas; Schmidt, Marcus; Thill, Marc; Untch, Michael; Wöckel, Achim; et al. (Geburtshilfe und Frauenheilkunde, 2025)
Background This study provides an indirect treatment comparison of ribociclib combined with non-steroidal aromatase inhibitors and ovarian function suppression (ribociclib + NSAI + OFS) vs. a frequently used treatment option in German clinical routine (tamoxifen ± OFS) in premenopausal patients with HR-positive (HR+), HER2-negative (HER2-) early breast cancer (BC). Material and Methods Data on premenopausal women treated with ribociclib and tamoxifen were derived from the NATALEE clinical trial (NCT03701334) and the retrospective German data collection CLEAR-B, respectively. NATALEE trial eligibility criteria were applied to the CLEAR-B dataset. Standardized mortality ratio weights were used for propensity score (PS) adjustment to balance study populations. All hazard ratios (HR) were calculated based on a 4-year-observation period for both treatment arms. Effectiveness endpoints comprised invasive and distant disease-free survival (iDFS, dDFS), recurrence-free survival (RFS), and overall survival (OS). Safety-related endpoints were treatment termination (TT) and toxicity-related TT (TTtox). For safety comparisons, the ribociclib arm was divided into groups that discontinued ribociclib + NSAI + OFS or ribociclib only. Results Significant beneficial effects favoring ribociclib + NSAI + OFS (n = 1115) over tamoxifen ± OFS (n = 822) were observed for all effectiveness outcomes (iDFS [HR = 0.5 (95% CI 0.35; 0.71); p < 0.01]; dDFS [HR = 0.52 (95% CI 0.35; 0.77); p = 0.01], RFS [HR = 0.42 (95% CI 0.29; 0.62); p < 0.01], OS [HR = 0.34 (95% CI 0.18; 0.63); p = 0.01]) during the 4-year-observation period. The effect of early treatment discontinuation showed no significant differences between ribociclib + NSAI + OFS and tamoxifen ± OFS (TT-a: HR = 1.2 [95% CI: 0.71; 2.01], p = 0.48; TTtox-a: HR = 0.54 [95% CI 0.22; 1.30], p = 0.23). Conclusion In this retrospective analysis, ribociclib + NSAI + OFS demonstrated advantages across all effectiveness endpoints, including OS, in premenopausal women with HR+, HER2- early BC, without increasing overall treatment discontinuation rates compared to tamoxifen ± OFS.
CRIS-Team Scopus Importer:2025-04-18
Keywords: early breast cancer; HER2-negative; HR-positive; indirect treatment comparison; ribociclib